Correlation of Serum Cholinesterase Levels with Clinical Severity and Outcomes in Paediatric Organophosphorus Poisoning - Dr. Ayush Muzalda; Dr. Ranjeet Ghasal, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Organophosphorus (OP) poisoning is a significant cause of morbidity and mortality in children, particularly in agricultural regions. Serum cholinesterase (ChE) activity is widely used for diagnosis, but its prognostic value in paediatric patients remains uncertain. Methods: A retrospective analysis was conducted on paediatric patients with confirmed OP poisoning admitted to a tertiary care centre over one year. Severity was assessed based on presenting symptoms, need for mechanical ventilation, and ICU stay duration. Serum ChE levels were measured at admission and serially thereafter. Correlations between ChE levels and clinical outcomes were analysed. Results: All patients had reduced serum ChE levels at admission (mean: XX ± SD U/L). No statistically significant correlation was found between baseline ChE levels and mortality, need for ventilatory support, or ICU stay duration (p > 0.05). Patients with extremely low ChE (<400 U/L) tended to have prolonged recovery and higher complication rates. Most survivors showed substantial improvement in ChE activity within 24–36 hours. Conclusion: In paediatric OP poisoning, serum ChE levels confirm the diagnosis but have limited prognostic value. Clinical assessment remains essential for severity grading and management.